2019
DOI: 10.1021/jacs.9b06010
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Effects of the Non-solvent on the Ligand Shell of Nanoparticles and Their Crystallization

Abstract: When nanoparticles (NPs) are assembled from solution, a common assembly method of choice is either solution destabilization or solvent evaporation technique. The destabilization of the NP solution by non-solvents results in the formation of faceted supercrystals (SCs) while periodic film-like assemblies are typically formed by solvent evaporation. Here, we reveal the effect of non-solvents in washing, dispersing, and crystallizing NPs. Small angle neutron scattering (SANS) is employed for monitoring the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 72 publications
(141 reference statements)
2
49
0
Order By: Relevance
“…However, an OA-triggered screening effect appears to weaken the strength of the direct interactions between inorganic NC cores so that the extent of orientational ordering is largely reduced in the nucleated fcc superlattice (Figure 10d,e) [55]. With a similar experimental control, large fcc supercrystals with multiple groups of orientational ordering were observed by various research groups [51,56], confirming the reliability of the derived guiding rules.…”
Section: Design Of Assembly Environments Towards the Collection Ofsupporting
confidence: 58%
See 2 more Smart Citations
“…However, an OA-triggered screening effect appears to weaken the strength of the direct interactions between inorganic NC cores so that the extent of orientational ordering is largely reduced in the nucleated fcc superlattice (Figure 10d,e) [55]. With a similar experimental control, large fcc supercrystals with multiple groups of orientational ordering were observed by various research groups [51,56], confirming the reliability of the derived guiding rules.…”
Section: Design Of Assembly Environments Towards the Collection Ofsupporting
confidence: 58%
“…Among a large variety of NC systems, PbS NCs have been extensively used to study the spontaneous NC self-assembly, and various superlattices have been observed accordingly, including fcc, bcc and a series of intermediate ones, such as the tetragonal superlattice [18,25,41,46,51,52,53,54,55]. Instead of covering many NC systems with too many details to distract attention, only PbS NCs with intermediate ratios of surface truncations are used as an example here to detail how the design and control of typical environments are experimentally made to activate specific NC interactions towards the ultimate harvest of a single superlattice of fcc or bcc at both small and large scales as desired (Figure 10) [46,55].…”
Section: Design Of Assembly Environments Towards the Collection Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] Excess ligands, even if added after completion of the SA, were also found to be able to affect interparticle spacings and the order in colloidal crystals already formed. [36] It is often the case that ligands are not bound covalently to the surface and thus can be replaced or removed by frequent washing steps [35,[42][43][44][45] and conversely that the presence of excess ligands affects SA. [36,46] Additionally, addition of excess ligands above the critical micelle concentration can cause the formation of micelles which can induce depletion attractions between the NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[28] In recent years many groups working on the self-assembly of NPs have highlighted the importance of ligands on the interactions between NPs and thus on what type of colloidal (liquid) crystal phases, with different symmetries and interparticle spacings they ultimately form. [29][30][31][32][33][34][35][36][37][38][39][40][41] The role of ligands on self-assembly was also recently reviewed. [29] Here we will only mention some typical examples of the role of ligands on SA as discussed in literature and almost all of relevance to the present…”
mentioning
confidence: 99%